AN ANALYSIS OF STUDENTS’ READING COMPREHENSION ACHIEVEMENT AT SECOND SEMESTER STUDENTS OF BHINNEKA PGRI UNIVERSITY IN THE ACADEMIC YEAR 2020/2021 - Nining Ayuk Agustin (Universitas Labuhanbatu, 2022)
To reading comprehension, especially long texts in foreign languages, some students have problems, such as being lazy and bored. If this problem persists, it will affect student achievement. This study was conducted with the aim of (1) to find how is the students’ reading comprehension achievement at second semester of Bhinneka PGRI University in the academic year 2020/2021. (2) to find what are the factors that affect the students’ reading comprehension achievement at second semester students of Bhinneka PGRI University in the academic year 2020/2021. The study used qualitative research to obtain valid data from 25 participants in class A at second semester in English Depatment. Researchers obtained data on reading comprehension test scores from the results of the TOEFL test questions given by researchers with an average value of 62. To test the truth, the researchers conducted interviews and questionnaire data. The results of the analysis are also through interviews with teachers and students, as well as questionnaires answered by students. It was concluded that learning reading skills in the second semester TOEFL test in English Depatment at the University of Bhinneka PGRI in the 2020/2021 academic year got poor achievements. Because they experience several problems in learning, namely difficulty in accessing the internet, lack of vocabulary that students have, and the material obtained are difficult to capture.